2003
DOI: 10.1021/jm020568d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of a Novel Series of Acylides:  3-O-(3-Pyridyl)acetylerythromycin A Derivatives

Abstract: A novel series of acylides, 3-O-(aryl)acetylerythromycin A derivatives, were synthesized and evaluated. These compounds have significant potent antibacterial activity against not only Gram-positive pathogens, including inducibly macrolide-lincosamide-streptogramin B (MLS(B))-resistant and efflux-resistant strains, but also Gram-negative pathogens, such as H. influenzae. 6,9:11,12-dicarbonate acylide 47 (FMA0122) was twice as active against H. influenzae than azithromycin, whereas it showed only moderate in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…A similar 3-O-(3-pyridyl)-acetyl derivative (78) (Fig. 18) of 8 was prepared [83], but antibacterial activity against Staphylococcus aureus and Streptococcus pneumoniae was lower than with the corresponding 14-membered derivative; only activity against H. influaenzae was improved.…”
Section: Scheme 13mentioning
confidence: 99%
“…A similar 3-O-(3-pyridyl)-acetyl derivative (78) (Fig. 18) of 8 was prepared [83], but antibacterial activity against Staphylococcus aureus and Streptococcus pneumoniae was lower than with the corresponding 14-membered derivative; only activity against H. influaenzae was improved.…”
Section: Scheme 13mentioning
confidence: 99%
“…The discovery of highly potent representatives of the third-generation of macrolides, like ketolides (Agouridas 1998), acylides (Tanikawa et al 2001;Tanikawa et al 2003), anhydrolides (Elliott et al 1998), etc., was a step forward to tackle the efflux problems Pestka & LeMahieu 1974a& 1974bPestka et al 1976;Allen. 1977;Van Bambeke et al 2008)' to (Tanikawa et al, 2001;Tanikawa et al, 2003), anhydrolides (Elliott et al, 1998), etc., was a step forward to tackle the efflux problems Pestka & LeMahieu 1974a& 1974bPestka et al, 1976;Allen.…”
Section: Introductionmentioning
confidence: 99%
“…1977;Van Bambeke et al 2008)' to (Tanikawa et al, 2001;Tanikawa et al, 2003), anhydrolides (Elliott et al, 1998), etc., was a step forward to tackle the efflux problems Pestka & LeMahieu 1974a& 1974bPestka et al, 1976;Allen. 1977;Van Bambeke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ketolides belong to a novel class of macrolide antibiotics with improved antibacterial activity against macrolide-resistant organisms (17). In this study, we have investigated for the first time the activity of RBx 14255, a novel ketolide (Fig.…”
mentioning
confidence: 99%
“…In summary, we have investigated and reported the activity of RBx 14255, a novel ketolide, against anaerobic bacteria for the first time. It was found that RBx 14255 is active against erythromycinand clarithromycin-resistant C. difficile strains, including the epidemic BI/NAP1/027 strain, and several bacterial species with different resistance patterns; these findings could indicate a special advantage of RBx 14255 over existing macrolides and ketolides (15,17). RBx 14255 is a novel antibacterial agent that prevents the growth of C. difficile by inhibiting protein synthesis and could be investigated for C. difficile treatment.…”
mentioning
confidence: 99%